2004
DOI: 10.1002/pbc.20004
|View full text |Cite
|
Sign up to set email alerts
|

MRI morphometric and neuropsychological correlates of long‐term memory in survivors of childhood leukemia

Abstract: Our hypothesis of deficits in both long-term memory and its neural substrates was not supported. It was concluded that the hippocampus, as an early developing structure, may be less vulnerable to chemotherapy treatment. Children surviving ALL are able to retain and retrieve once learned information comparable with peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…(Von der Weid,2001; Langer et al,2002; Hill et al,2004; Spiegler et al,2006; Mahone et al,2007; Aukema et al,2009; Kadan-Lottick et al,2009; Kadan-Lottick et al,2010; Robinson et al,2010; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Krull et al,2013; Lewis et al,2013; Ross et al,2013; Schuitema et al,2013; Edelmann et al,2014; Elalfy et al,2014) There were only 4 longitudinal studies that evaluated survivors’ neurocognitive changes from active treatment to post-treatment survivorship phase. (Kingma et al,2001; Harila et al,2009; Halsey et al,2011; Lewis et al,2013) Most studies focused on a pure sample of survivors who received chemotherapy-only treatment protocols while others included separate populations of ALL survivors who received CRT(Kingma et al,2001; Von der Weid,2001; Langer et al,2002; Spiegler et al,2006; Harila et al,2009; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2011; Daams et al,2012; Krull et al,2013; Schuitema et al,2013; Edelmann et al,2014) or patients of other cancer types.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Von der Weid,2001; Langer et al,2002; Hill et al,2004; Spiegler et al,2006; Mahone et al,2007; Aukema et al,2009; Kadan-Lottick et al,2009; Kadan-Lottick et al,2010; Robinson et al,2010; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Krull et al,2013; Lewis et al,2013; Ross et al,2013; Schuitema et al,2013; Edelmann et al,2014; Elalfy et al,2014) There were only 4 longitudinal studies that evaluated survivors’ neurocognitive changes from active treatment to post-treatment survivorship phase. (Kingma et al,2001; Harila et al,2009; Halsey et al,2011; Lewis et al,2013) Most studies focused on a pure sample of survivors who received chemotherapy-only treatment protocols while others included separate populations of ALL survivors who received CRT(Kingma et al,2001; Von der Weid,2001; Langer et al,2002; Spiegler et al,2006; Harila et al,2009; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2011; Daams et al,2012; Krull et al,2013; Schuitema et al,2013; Edelmann et al,2014) or patients of other cancer types.…”
Section: Resultsmentioning
confidence: 99%
“…(Kingma et al,2001; Harila et al,2009; Halsey et al,2011; Lewis et al,2013) Most studies focused on a pure sample of survivors who received chemotherapy-only treatment protocols while others included separate populations of ALL survivors who received CRT(Kingma et al,2001; Von der Weid,2001; Langer et al,2002; Spiegler et al,2006; Harila et al,2009; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2011; Daams et al,2012; Krull et al,2013; Schuitema et al,2013; Edelmann et al,2014) or patients of other cancer types. (Aukema et al,2009; Kadan-Lottick et al,2010) The majority of the included studies had sample sizes between 10 to 50 subjects,(Kingma et al,2001; Langer et al,2002; Hill et al,2004; Mahone et al,2007; Aukema et al,2009; Harila et al,2009; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Schuitema et al,2013; Edelmann et al,2014) with the exception of 4 studies with a larger cohort of more than 100 subjects(Von der Weid,2001; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2013) and 3 studies with less than 10 subjects. (Lewis et al,2012; Lewis et al,2013; Ross et al,2013) Most the studies reported survivors’ mean duration of time since diagnosis, which ranged between 5 and 22 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the association of leukoencephalopathy and neurocognitive disturbances has been indeterminate. Child survivors of systemic ALL treated with methotrexate often suffer with intellectual impairment and learning disabilities [53][54][55]. Adults, most often treated with high-dose intravenous methotrexate for primary central nervous system lymphoma, develop a syndrome closely resembling normal pressure hydrocephalus characterized by disturbances of memory, attention, and gait, and urinary incontinence.…”
Section: Methotrexatementioning
confidence: 99%
“…Hippocampal dedritic spine damage is found after single-dose administration of cyclophosphamide in hippocampal slices, and causes transient impairment of long-term potentiation (Lee et al, 2006). Clinically, reduced hippocampal volume and loss of neurogenesis have been found in chemotherapy treated colon cancer patients (Schneiderman, 2004) and brain tumor patients 37 , respectively, though no clear changes were found in ALL survivors (Hill et al, 2004). However, the attention and memory deficits present in ALL patients might suggest a functional deficit even if no structural changes are clearly defined.…”
Section: Further Directions: Neuroprotective and Restorative Treatmentsmentioning
confidence: 99%